Analytical model of the two-mass above resonance system of the eccentric-pendulum type vibration table - Lanets, O.S.; Dmytriv, V.T.; Borovets, V.M.; Derevenko, Iryna A. (Zielona Góra: Uniwersytet Zielonogórski)
The article deals with atwo-mass above resonant oscillatory system of an eccentric-pendulum type vibrating table. Based on the model of a vibrating oscillatory system with three masses, the system of differential equations of motion of oscillating masses with five degrees of freedom is compiled using generalized Lagrange equations of the second kind.
Keywords: two-mass system; eccentric-pendulum drive; Lagrange equation; Rosenbrock method; vibrations